STUDENTS' READINESS TO MASTER 21ST-CENTURY SKILLS - Siska Wulandari; Anna Damayanti; Muhammad Sirozi (LP2M IAI Al-Khairat Pamekasan, 2026)
The development of information technology, globalization, and the industrial revolution 4.0 requires the education system to prepare students with relevant 21st century skills. These skills are in line with the four pillars of UNESCO education, namely learning to know, learning to do, learning to be, and learning to live together, which includes critical thinking skills, problem solving, creativity, communication, collaboration, information literacy, and metacognition. This article aims to examine the readiness of students to master 21st century skills and the factors that influence them. The method used is a literature study by analyzing various relevant scientific sources. The results of the study show that students' readiness is influenced by four main factors: relevant curriculum, innovative learning strategies, integration of technology in the teaching and learning process, and a conducive learning environment. The achievement of 21st century skills can be realized through project- or problem-based learning, personalization of learning, strengthening collaboration and communication, empowerment of metacognition, and design of learning activities that are contextual and relevant to the real world. The main principle of 21st century learning emphasizes that learning must be student-centered, collaborative, contextual, and integrated with people's lives. These various skills need to be taught explicitly and planned. The role of teachers is crucial in implementing learning that is able to facilitate the development of these skills. In conclusion, educational institutions need to develop adaptive and innovative learning models so that students are able to face global challenges in the future and become competent, creative, and highly competitive individuals.